2018
DOI: 10.5897/ijps2017.4689
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver monometallic and copper-silver bimetallic nanoparticles using Kigelia africana fruit extract and evaluation of their antimicrobial activities

Abstract: Aqueous extract of Kigelia africana fruits have been utilized in the syntheses of silver nanoparticles (AgNPs) and copper-silver bimetallic nanoparticles (Ag-CuNPs). The synthesized nanoparticles have been characterized using UV-vis, Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy/energy dispersive X-ray analysis (SEM/EDX), x-ray diffration (XRD) and transmission electron microscopy (TEM). The antimicrobial activities have been evaluated against both Grams-negative and Grams-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 54 publications
(64 reference statements)
0
10
0
1
Order By: Relevance
“…Moreover, this process for AgNPs synthesis is economic, time efficient and straight forward. Phoenix dactylifera , 228 strawberry, 229 Ginseng-berry, 230 Kigelia africana 231 and Chaenomeles sinensis 232 fruit extract were also successfully utilized for the green synthesis of spherical AgNPs with high antimicrobial activity. Ginseng-berry fruit extract derived AgNPs showed greater ZOI against S. aureus (12.3 mm) compared to E. coli (11 mm).…”
Section: Plant-mediated Biogenic Synthesis Of Agnps and Their Antimic...mentioning
confidence: 99%
“…Moreover, this process for AgNPs synthesis is economic, time efficient and straight forward. Phoenix dactylifera , 228 strawberry, 229 Ginseng-berry, 230 Kigelia africana 231 and Chaenomeles sinensis 232 fruit extract were also successfully utilized for the green synthesis of spherical AgNPs with high antimicrobial activity. Ginseng-berry fruit extract derived AgNPs showed greater ZOI against S. aureus (12.3 mm) compared to E. coli (11 mm).…”
Section: Plant-mediated Biogenic Synthesis Of Agnps and Their Antimic...mentioning
confidence: 99%
“…In the current work, most of SPR peaks are within the anticipated wavelength range, however, some researchers have reported SPR peaks below 400 nm for their synthesized nanoparticles [9,15,31,41,42]. The absorbance bands below 400 nm are probably due to absorption of silver ions, complexes, impurities and plant phytochemicals.…”
Section: Uv-visible Spectrophotometrymentioning
confidence: 57%
“…It is evident that the stability of plant metabolites requires working at ambient temperature. However, to shorten the synthesis time and enhance complete conversion of Ag + to Ag 0 , some researchers have attempted synthesis at higher temperatures [8,9,14,[28][29][30][31][32][33]. Interestingly, Krishnan et al has synthesized silver nanoparticles from Piper nigrum at room temperature, 40, 60 and 80 °C and studied the surface plasmon resonance (SPR) of the resultant nanoparticles by UV spectroscopy and found that nanoparticles synthesized at 80 °C gave an intense surface plasmon resonance band [28].…”
Section: The Effect Of Temperaturementioning
confidence: 99%
“…The main issues of AgCu NA preparation are high antibacterial efficacy, low toxicity, and high stability, which are strongly associated with the physicochemistry of the NAs and their stabilizers [ 23 ]. A recent study showed that biosynthesized AgCu NAs might have even better antibacterial efficacy [ 7 , 9 , 24 , 25 , 26 , 27 , 28 ]. These studies used plant extracts to synthesize AgCu NAs or bacteria to reduce Ag + and Cu 2+ and stabilize the AgCu NAs [ 12 , 29 ].…”
Section: Introductionmentioning
confidence: 99%